Cataract as the First Manifestation of Insulin Dependent Diabetes Mellitus: Doi: 10.36351/pjo.v40i4.1828 - Aljawhara T. Aldamri; Mohammed Alshamrani; Saleh A. Al-Khaldi (Pakistan Journal of Ophthalmology, 2024)
An 8-year-old girl presented with blurry vision. Examination revealed impaired visual acuity (VA) in both eyes and significant lamellar and posterior subcapsular cataracts requiring surgery. Preoperative laboratory tests indicated elevated urine and blood glucose levels, leading to a diagnosis of insulin-dependent diabetes mellitus by a paediatric endocrinologist. She began insulin treatment and underwent lens aspiration with posterior chamber intraocular lens implantation. Postoperatively, her VA improved to 20/30 in the right eye and 20/60 in the left eye.